The Association Between Lipid Profiles and Atherogenic Index with Diabetic Foot Severity According to the Wagner-Meggitt Classification at Adam Malik Hospital - Wilonna, Almira; Pase, M Aron; Lubis, Dian Anindita (TALENTA Publisher, Universitas Sumatera Utara, 2025)
ABSTRACTIntroduction: Diabetic foot is a serious complication that leads to ulcers and amputations. Identifying risk factors, such as lipid profiles and atherogenic indices is crucial for prevention and treatment for cardiovascular disease and peripheral arterial disease. This study aims to investigate the relationship between lipid profiles and atherogenic indices with the severity of diabetic foot, categorized by the Wagner-Meggitt classification, at Adam Malik Hospital. Methods: This analytical observational study with cross-sectional design was conducted at Adam Malik Hospital, involving 70 diabetic foot patients. Data were collected from medical records, focusing on lipid profiles. Atherogenic indices were calculated as ratios: TC/HDL, TG/HDL, and LDL/HDL. The severity of diabetic foot was measured using the Wagner-Meggitt classification. Statistical analysis included Chi-square and Spearman's rho tests. Results: Of the 70 patients, most were aged 51-60 (41.4%), male (60%), and had normal BMI (57.1%). There was a significant correlation between diabetic foot severity and triglyceride levels (p=0.0002, r=0.358) as well as the TC/HDL ratio (p=0.02, r=-0.277). However, no significant relationships were found for total cholesterol (p=0.533), HDL (p=0.254), LDL (p=0.533), the TG/HDL ratio (p=0.158), or the LDL/HDL ratio (p=0.92). Discussion: In this study, 60% of the participants were male. The findings align with previous studies, demonstrating a correlation between elevated triglycerides and lipid profile abnormalities with the severity of diabetic foot ulcers. Conclusion: Triglycerides and the total cholesterol/HDL ratio are significantly associated with the severity of diabetic foot based on the Wagner-Meggitt classification. Keywords: diabetic foot; lipid profile; atherogenic index; Wagner-Meggitt